Fast growth synthesis of mesoporous germanium films by high frequency bipolar electrochemical etching. (1st April 2017) - Bioud, Youcef A.; Boucherif, Abderraouf; Belarouci, Ali; Paradis, Etienne; Fafard, Simon; Aimez, Vincent; Drouin, Dominique; Arès, Richard
Abstract: Mesoporous germanium (MP-Ge) has been predicted to play an important role in a wide range of potential applications. These porous Ge networks are characterized by physical and chemical properties that contrast with their bulk counterpart. For more than two decades, the methods that were used to synthesize these materials were extremely slow and yield non-uniform layers, which limit their applications. Here we demonstrate the synthesis of thick MP-Ge films with high growth rate (up to 300 nm/min) by using high-current density and high-frequency bipolar electrochemical etching. An optimized nucleation procedure is also reported. It enables a much better lateral homogeneity of the MP-Ge films. Following these results a refined electrochemical Ge etching model is proposed. The model is confirmed by Fourier Transform Infrared Spectroscopy and Cyclic Voltammetry measurements. Reflectivity measurements were also used to demonstrate that the effective refractive index of MP-Ge can be adjusted as a function of layer porosity. It has been reduced down to 1.76 due to the presence of the mesopores. Finally, a basic interferometric porous Ge sensor is demonstrated, a detection sensitivity of 711 nm/RIU was measured upon exposure to glycerol-water solutions.